Lithospheric evolution, thermo-tectonic history and source-rock maturation in the Gippsland Basin, Victoria, southeastern Australia. Issue 1 (2nd January 2022) - Röth, J.; Parent, A.; Warren, C.; Hall, L. S.; Palmowski, D.; Koronful, N.; Husein, S. S.; Sachse, V.; Littke, R.
Abstract: A fully integrated 3D basin model was built to study the lithospheric structural evolution and the thermal history of the offshore part of the Gippsland Basin to investigate the type, timing and magnitude of its initial opening mechanism and their effects on source rocks. The applied workflow included seismic interpretation of major faults and magmatic features, seismic reinterpretation of existing main stratigraphic boundaries and adjustment of the basement topography. Different scenarios for a McKenzie-type basal heat flow evolution were tested based on a two-step inversion approach, which translates the thickness changes of lithospheric layers into basal heat flow. Finally, a crustal layer model was assigned to the existing 3D numerical basin model and the effects on thermal maturation of petroleum source rocks were investigated. The results of the calibrated inversion model suggest intense lithospheric stretching and mantle upwelling during the Early Cretaceous caused initial breakup and subsidence of the Gippsland Basin. This syn-rift phase was accompanied by increasing basal heat flow from initially ∼ 50 mW/m 2 to a maximum of 80–90 mW/m 2 . The resulting upwelled Moho with an associated crustal thickness of locally only 8 km agrees with geophysical observations. Elevated paleogeothermal gradients between 50 and 60 °C/km prevailed from ca 120 to 80 Ma. Episodes of compression, uplift, erosion, and thermal subsidence resulted in fast and continuous cooling during the early post-rift and a constant basal heat flow of 45–50 mW/m 2 since the Eocene. Two main pulses of petroleum generation were identified in the Paleocene and in the Miocene–Pliocene. This novel two-step crustal layer inversion method allows a detailed reconstruction of the thermal history of rift basins and can provide useful information about the maturation of petroleum source rocks. KEY POINTS: A temperature history reconstruction of the Gippsland Basin is given based on a large-scale numerical 3D model. Tectonically induced strong variability in paleoheat flows is recognised. Strong maturation and petroleum generation developed during the Paleogene and Neogene.